Feasibility and acceptability of ice plant intensive cream in preventing hand-foot syndrome in breast cancer patients undergoing Doxorubicin and/or Docetaxel therapy: a randomized controlled pilot study - Marcela Winkler; Renée Arnhold; Dennis Anheyer; Christel Idler; Felicitas Löffler; Georg Sauer; Claudia Löffler; Holger Cramer (Frontiers in Oncology, 2026)
Introduction Hand-Foot Syndrome (HFS) is a common side effect in patients undergoing chemotherapy, particularly with Doxorubicin and Docetaxel and can substantially impair quality of life. This study aimed to assess the feasibility and acceptability of using Ice Plant Intensive Cream ( Mesembryanthemum crystallinum ) to prevent HFS in breast cancer patients, within a predefined recruitment target of 36 participants. Methods In this randomized controlled pilot study, patients with breast cancer scheduled to receive treatment with doxorubicin or docetaxel were enrolled. Participants were randomly assigned either to an intervention group, which followed standard HFS prevention plus Ice Plant Intensive Cream to the hands and feet three times daily during chemotherapy, or a control group that received standard HFS prevention alone. Feasibility endpoints included recruitment rate, inclusion rate, retention, adherence to the intervention, and completeness of data collection. Secondary exploratory endpoints included HFS severity, skin-related symptoms, and quality of life. Results Between January and November 2023, 330 patients were screened during tumor board meetings, of whom 58 met the eligibility criteria. Ultimately, 13 patients (22.4% of eligible) consented and were enrolled, indicating that neither the predefined recruitment target nor the randomization feasibility criterion were met. Most non-participation was attributable to patient overload during the diagnostic phase or initiation of chemotherapy before contact. Once enrolled, feasibility metrics related to retention, adherence, and data completeness were achieved, with a dropout rate of 15%, protocol adherence of 100% among participants who completed the study, and more than 90% completeness of scheduled assessments. Conclusion The overall study was not feasible as designed, primarily due to recruitment limitations. However, once patients were enrolled, intervention procedures, data collection, and protocol adherence were fully feasible. Optimization of recruitment timing and earlier patient engagement during the diagnostic phase are recommended for future confirmatory trials. Clinical Trial Registration https://clinicaltrials.gov/study/NCT05755646 , identifier NCT05755646.